The Enhancing Students’ Personal Branding through Public Speaking and Digital Marketing Training at SMK Muhammadiyah 2 Yogyakarta: Meningkatkan Personal Branding Siswa melalui Pelatihan Public Speaking dan Digital Marketing di SMK Muhammadiyah 2 Yogyakarta - Sheila Lestari Giza Pudrianisa; Yulinda Erlistyarini; Monika Pretty Aprilia; Windy Oktavia Nur Cahyaningrum; Wilhelmus Feliksitus Sea Putrama; Bribta Nanik Muninggar (Room of Civil Society Development, 2026)
Vocational high school students are expected to possess not only technical competencies but also communication skills, digital literacy, and the ability to build professional self-presentation in the digital era. However, students at SMK Muhammadiyah 2 Yogyakarta still faced limitations in public speaking, digital marketing literacy, and the productive use of social media for personal branding. This community service program aims to improve students’ public speaking skills, digital marketing understanding, and personal branding awareness. The program involved 33 students from grades X and XI and was implemented through observation, interactive workshops, practice, simulation, and evaluation using pre-test and post-test instruments. The evaluation consisted of 14 questions, covering seven items on digital marketing and seven items on public speaking. The results showed that the training improved students’ understanding across several indicators, particularly in digital marketing objectives, digital marketing actors, and public speaking concepts, as reflected in the pre-test and post-test evaluation. The program indicates that integrating public speaking and digital marketing training can support students’ personal branding and enhance their readiness to compete in the digital workforce.